STRATEGI PENGEMBANGAN PARIWISATA KABUPATEN SOLOK SELATAN - Eka Putri, Femitri; Ariadi, Budi; Syarkawi, Ikhsan; Mulyati, Rahmi (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
Regarding the promotional activities carried out by the Tourism and Culture Office of South Sojok Regency in an effort to attract tourism to visit tourist objects in South Solok Regency. This Promotion Strategy is carried out using several media, including Print Media (Procurement of Brochures and other information materials), Electronic Media (Radio, TV, VCD, Internet), Outdoor Media in Exhibition Spaces, Festivals and Other Promotional Activities). In the research method of collecting data obtained descriptively which is primary data and secondary data, data analysis is based on SWOT analysis. From the SWOT Analysis it was concluded that. The main strength of tourism in Solok Selatan Regency is in the form of nature tourism and tours. culture, history, and tourist attractions. Kefernah Tourism Kab. South Solok is . The lack of supporting facilities and infrastructure for South Solok Tourism has not reached the level of; damaged road conditions and lack of innovative response to tourists, lack of information and exploitation of tourists, lack of human resources who are experts in tourism and far rivals from cross-Sumatra transportation routes. The threat of Solok Seiatan Tourism is having tourist objects that are the same as other regions, tourist objects that are not yet adequate and low public knowledge and awareness about tourism. have specific art and culture.